180k views
0 votes
-x = 2 - 3x +3
Please explain solution in detail as well as steps to getting there. Thank you!

User Preetam
by
5.6k points

2 Answers

2 votes

Answer:

2.5

Explanation:

-x=2-3x+3

Add 3x to both sides:

2x=5

Divide both sides by 2:

x=2.5

Hope this helps!

User Dominic Cronin
by
4.5k points
1 vote

Answer:

x = 2.5

Explanation:

-x = 2 - 3x +3

Combine like terms

-x = -3x+5

Add 3x to each side

-x+3x = -3x+3x+5

2x = 5

Divide by 2

2x/2 = 5/2

x = 2.5

User QiAlex
by
5.0k points